The effect of a multimodal multicomponent Prehabilitation program in Older adults with Chronic limb-threatening Ischemia (POCI-study): A study protocol for a multicenter randomized controlled trial - Seline Verbaan; Miriam C. Faes; Elke T. A. M. van Delft; Alexander L. Kooiman; Patrick W. H. E. Vriens; Hidde Jongsma; Ewout W. Steyerberg; Wilbert B. van den Hout; Lijckle van der Laan (PLoS ONE, 2026)
Chronic limb threatening ischemia (CLTI) in older adults is associated with severe morbidity and high mortality. The rising prevalence is largely driven by the aging population and confronts healthcare systems with challenges like increasing demand for chronic care, staff shortage and rising healthcare costs. To improve post-operative outcomes and reduce the burden on healthcare systems, multimodal prehabilitation has gained interest and has the potential to improve post operative outcomes. However, evidence of the effect in older adults with CLTI remains scarce. The aim of this study is to determine whether a multimodal multicomponent prehabilitation program (MMPP) reduces length of stay and improves clinical, patient-reported and economic outcomes of older adults with CLTI. We developed a multicenter randomized controlled trial, with embedded cost-effectiveness analyses.. CLTI-patients aged 65 years or older, planned for revascularization, and their primary informal caregiver (IC) will be eligible. A total of 300 patients will be randomized to receive either standard preoperative care or a 2-week MMPP. All patients receive a general health screening. The MMPP includes physiotherapy and, if indicated, referral to a geriatrician, dietician or smoking-cessation coach, ferric carboxymaltose infusion or pre-arranged homecare. The primary outcome is length of stay. Exploratory secondary outcomes include minor complications, quality of life of patient and IC and health related quality of life. Descriptive secondary outcomes include 30-day and 6-month mortality, major complications, readmissions, burden on the IC, cost-effectiveness; and experiences and preferences regarding shared decision making. To the best of our knowledge, this is the first randomized controlled trial to evaluate the effect of an MMPP within older CLTI-patients. Findings will inform healthcare professionals whether an MMPP should be implemented in routine vascular surgical practice to reduce length of stay and improve clinical and patient-centered outcomes. The study is registered at the International Clinical Trials Registry Platform (NL-OMON58069).